2017
DOI: 10.1186/s12937-017-0264-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of whole-blood polyunsaturated fatty acids among young children with moderate acute malnutrition

Abstract: BackgroundSevere acute malnutrition (SAM) has been associated with low polyunsaturated fatty acid (PUFA) status. However, investigations regarding PUFA status and correlates in children with moderate acute malnutrition (MAM) from low-income countries are scarce. The aim of this study was to describe whole-blood PUFA levels in children with moderate acute malnutrition (MAM) and to identify correlates of PUFAs.MethodsWe conducted a cross-sectional study using baseline data from a prospective nutritional interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 43 publications
3
27
1
Order By: Relevance
“…In addition, we found that PUFA status, especially n‐3 LC‐PUFAs, were associated with better development scores. As we have previously reported, family diets in our study population were predominantly cereal‐based with low consumption of animal‐source foods including cow's milk, fish, vegetable oils, and other sources of n‐3 PUFA (Yaméogo et al, ). Consequently, overall PUFA deficiency was not found to be a problem in this population, but levels of n‐3 LC‐PUFA were low and potentially a limiting factor for the development of children.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In addition, we found that PUFA status, especially n‐3 LC‐PUFAs, were associated with better development scores. As we have previously reported, family diets in our study population were predominantly cereal‐based with low consumption of animal‐source foods including cow's milk, fish, vegetable oils, and other sources of n‐3 PUFA (Yaméogo et al, ). Consequently, overall PUFA deficiency was not found to be a problem in this population, but levels of n‐3 LC‐PUFA were low and potentially a limiting factor for the development of children.…”
Section: Discussionmentioning
confidence: 60%
“…There was very little variation in other socio‐economic characteristics (e.g., 99% lived in a house owned by one of the household members and 99% used coal as cooking fuel). Data on anthropometry, MAM‐defining criteria, body composition, LC‐PUFA, Hb, iron status, and morbidity are presented in Table for information and described in more detail in previous publications (Cichon et al, ; Fabiansen, Yaméogo, Iuel‐Brockdorf, et al, ; Yaméogo et al, ); 27% of children were moderately stunted (HAZ between −2 and −3) and 10% severely stunted (HAZ <−3). Morbidity was very common with 38% recently ill and 40% having a positive malaria test on the day of MDAT assessment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…QC for metabolomics measurements was performed as previously described [ 20 ]. For GPL-FA, we calculated the sums of SFA (∑SFA), MUFA (∑MUFA), PUFA (∑PUFA) and the ratios: Mead acid (C20:3n-9) to arachidonic acid (AA, C20:4n-6) (marker of EFA deficiency) [ 21 , 22 ]; AA to linoleic acid (LA) (C20:4n-6/C18:2n-6) (a marker of PUFA to LC-PUFA conversion by Δ-6 desaturase, Δ-5 desaturase, and elongase activities) [ 23 , 24 ]; eicosapentaenoic acid (EPA, C20:5n-3) to AA; n-6 docasapentaenoic to docosahexaenoic acid (n-6 DPA/DHA, C22:5n-6/C22:6n-3): and n-6 to n-3 PUFA (markers of n-3 PUFA status) [ 25 , 26 ]. For the PL species, we calculated ∑PC.aa, ∑PC.ae, ∑lyso.PC.a, ∑lyso.PCe, ∑PC, and ∑SM.…”
Section: Methodsmentioning
confidence: 99%